Sociodemographic and dietary factors influencing overweight and obesity in school going children aged 10 to 15 years: a cross sectional community based study - R. L. C., Amarnath; K., Shilpa; Ugargol, Amit R.; Bandlamudi, Sowjanya (International Journal Of Community Medicine And Public Health, 2017)
Background: Childhood obesity as a rampant public health problem as it is affecting both developed and developing countries. Understanding the trends in obesity prevalence among children, contributing factors and developing strategies for successful interventions is the need of the hour. Hence the present study was aimed at understanding the implication of dietary and socio-demographic factors influencing overweight and obesity among 10-15 year old school children. Methods: The study was a cross sectional study, undertaken in eight private schools of Belgaum City, Karnataka from January 2010 to December 2010. School children of sixth to tenth standard aged between 10 to 15 years were included. Children were interviewed by the investigator. Examination was carried out which included general physical examination, measurement of height, weight, waist circumference, hip circumference, blood pressure and other vital signs. Overweight and obesity were defined basing on Based on WHO and International obesity task force (IOTF) BMI cut-off standards for Asia and India. Results: A total of 600 children were included of which 52.33% were males. Majority of the study subjects belonged to socio economic class I and II. About 65.67% of students belonged to nuclear family. The prevalence of overweight and obesity was 18.83% in study population. Out of this overweight contributed 11.33% and obesity contributed 7.5%.The odds of overweight and obesity was higher in females (OR=1.19), In children aged 13 years (OR=3.21), in children belonging to Sikh community (OR=6.26) and in children with socio economic class II (OR=1.65). Children from joint family (OR=0.70) and third generation family (OR=0.29) had lower odds of overweight and obesity compared to children from nuclear families. Daily consumption of snacks between meals (OR=2.42), sweets (OR=1.985), ice-cream (OR=1.667), fast foods (OR=3.062) and beverages (OR=4.80) were strongly associated with increased risk of overweight and obesity in study population. Daily consumption of fruits (OR=0.095) and vegetables (OR=0.166) and pulses (OR=0.690) was associated with reduced risk of overweight and obesity in study population (Table 4). Conclusions: Overall the study findings reveal that children had a relatively higher prevalence of overweight and obesity. Regular intake of fast foods, beverages, snacks between the meals and ice creams was associated with higher risk of obesity in study population. Regular consumption of fruits, vegetables and pulses had strong negative association with overweight and obesity in study population.